Analysis of Students’ Attitudes Toward Physics Achievement - Khusaini, Khusaini; Azizah, Nur; Yogihati, Chusnana Insjaf (Universitas Muhammadiyah Makassar, 2024)
Attitudes plays an important role in influencing student achievement in physics education. However, there is limited study investigating the effect of students’ attitudes on physics achievement in Indonesia. Therefore, this research aimed to investigate the correlation between students' attitudes towards physics learning achievement. The research used a quantitative descriptive approach through survey methods. The research sample was obtained by simple random sampling of as many as 35 students of class XI IPA 2, consisting of 17 men and 18 women. Data collection used a student attitude questionnaire instrument. The study showed that student’s attitudes have an average of 61 with the highest student's attitude being 90 and the lowest student's attitude being 30. The results of student achievement in the form of physics test scores have an average of 67 with the highest score being 100 and the lowest score being 36. The results of the correlation test analysis obtained a score significance (p 0.05) with a correlation coefficient of 0.576. So, it can be concluded that there is a positive correlation and a fairly strong category between students' physics attitudes and students' physics achievements. This shows that the higher the student's attitude towards physics, the higher the student's achievement will be.